Methodological application of the interdisciplinary approach in the study of the coexistence of science and religion - Лимар, В. (Київський національний університет імені Тараса Шевченка, 2024)
B a c k g r o u n d . The article is devoted to the methodology in the study of science and religion, which takes place only in the constructive dialogue of these two existential manifestations. Despite this, three versions of the interaction of science and religionare considered, which took place during the temporal course of history. And only from the middle of the 20th century, when religion and science alternately lost dominance in society, a relatively equal dialogue between these manifestations of human activity began, forced by the necessity of losing their authority among European civilization. M e t h o d s . The research uses empirical and theoretical methods of observation and description, analysis and generalization. R e s u l t s . Against the background of highlighting the views of modern thinkers about the coexistence of these seemingly incompatible and opposite areas of human existence, the application of an interdisciplinary approach to the study of urgent issues of both science and religion is analyzed. Since both science and religion are intellectual manifestations of human activity, which creates a multi-layered reality, where each of these realms has its own object of study / honoration, then in methodology they must rely on newgeneral anthropological discoveries and achievements. In this context, attention is paid to synergy, interdisciplinarity and transdisciplinarity. Each of these interdisciplinary approaches to research methodology is considered separately and their transformation with the rapid intellectual progress of the middle of the 20th – 21st centuries are followed. Attention is also paid to the risks of their application in relation to the study of religion, since science imposes its stereotyped ideason the study of the world and on religious practices, which, by their very nature, are far from the goal and tasks of scientific research. This is because theology can safely be considered a religious science – a kind of science within religion at a time whenother forms were banned and censored. The inquisitive human mind was looking for any solution to its needs, which were later separated into pure science, and left for religion the role of mystical practices of communication with the Deity and introspection. But in the general understanding of religion, interdisciplinary approaches are very important new achievements that should not be neglected and their results equated with eclecticism. C o n c l u s i o n s . In support of the given arguments and the results of the research of this article, the opinions of competent foreign and domestic researchers in the field of dialogue between science and religion are given, who in some places categorically expressed the expediency of coexistence and cooperation of these areas, but who did not deny their joint and individual expediency in the development of human being.

В с т у п . Присвячено методології у дослідженні науки та релігії, яка є тільки в разі конструктивного діалогу цих двох екзистенційних проявів. Попри це розглядаються три варіанти взаємодії науки та релігії, які існували протягом темпорального плину історії. І лише від середини ХХ ст., коли почергово і релігія, і наука втрачали домінування у соціумі, розпочинається вимушений необхідністю втрати їхнього авторитету серед європейської цивілізації, відносно рівноправний діалог цих проявів людської діяльності. М е т о д и . Використано емпіричні та теоретичні методи спостереження та описування, аналізу і узагальнення. Р е з у л ь т а т и . На тлі висвітлення поглядів сучасних мислителів про співіснування цих, здавалося б, несумісних і протилежних царин людського буття, проаналізовано застосування міждисциплінарного підходу для дослідження нагальних питань як науки, так і релігії. Оскільки і наука, і релігія є інтелектуальними проявами людської діяльності, яка творить багатошарову реальність, де кожна із цих царин має свій власний об'єкт дослідження / вшанування, то і в методології вони повинні спиратись на нові загальні антропологічні відкриття та досягнення. У цьому контексті приділено увагу синергетиці, міждисциплінарності та трансдисциплінарності. Окремо розглянуто кожен із цих наддисциплінарних підходів до методології дослідження і простежено їх трансформацію зі стрімким інтелектуальним прогресом середини ХХ-го – ХХІ-го століть. Також вивлено ризики їх застосування щодо дослідження релігії, оскільки наука накладає свої шаблонні уявлення відносно дослідження світу і на релігійні практики, котрі за своєю суттю далекі від мети та завдань наукових досліджень. Це відбувається тому, що богослов'я впевнено можна вважати релігійною наукою – своєрідною наукою у межах релігії на той час, коли інші форми були заборонені та цензуровані. Допитливий людський розум шукав будь-який вихід своїм потребам, котрі згодом виокремились у чисту науку, і залишити для релігії роль містичних практик спілкування із Божеством та інтроспекції. Але в загальному розумінні релігії міждисциплінарні підходи є дуже важливими новими досягненнями, якими не слід нехтувати і прирівнювати їх результати до еклектизму. В и с н о в к и . На підтвердження наведених аргументів та результатів дослідження наведено думки компетентних закордонних та вітчизняних дослідників у галузі діалогу науки та релігії, котрі подекуди категорично висловлювались стосовно доцільності співіснування і співпраці цих царин, але які не заперечували все ж їх спільної та осібної доцільності в розвитку людського буття.
Методологічне застосування міждисциплінарного підходу під час дослідження співіснування науки та релігії
Keywords: science; religion; synergy; interdisciplinarity; transdisciplinarity; наука; релігія; синергетика; міждисциплінарність; трансдисциплінарність